2022
DOI: 10.1080/19490976.2022.2083419
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota in mucosa and feces of newly diagnosed, treatment-naïve adult inflammatory bowel disease and irritable bowel syndrome patients

Abstract: The knowledge on how gut microbes contribute to the inflammatory bowel disease (IBD) at the onset of disease is still scarce. We compared gut microbiota in newly diagnosed, treatment-naïve adult IBD (Crohn’s disease (CD) and ulcerative colitis (UC)) to irritable bowel syndrome (IBS) patients and healthy group. Mucosal and fecal microbiota of 49 patients (13 UC, 10 CD, and 26 IBS) before treatment initiation, and fecal microbiota of 12 healthy subjects was characterized by 16S rRNA gene sequencing. Mucosa was s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 84 publications
(104 reference statements)
0
11
0
1
Order By: Relevance
“…Metabolomic and metagenomic studies using stool and serum samples of patients with IBS showed that enrichment of R. gnavus was strongly associated with low levels of dihydropteroic acid, an important intermediate in folic acid synthesis, contributing to metabolic dysregulation in IBS pathology (Han et al 2022a ). The role of R. gnavus (amongst other species) as a potential biomarker for discriminating disease phenotypes was further confirmed in a 16S rRNA gene sequencing-based comparison of gut faecal and mucosa microbiota in newly diagnosed, treatment-naïve adults with IBD or IBS (13 UC, 10 CD, and 26 IBS) and in a healthy group (Cipcic Paljetak et al 2022 ).…”
Section: Association Between R Gnavus and Diseasesmentioning
confidence: 84%
“…Metabolomic and metagenomic studies using stool and serum samples of patients with IBS showed that enrichment of R. gnavus was strongly associated with low levels of dihydropteroic acid, an important intermediate in folic acid synthesis, contributing to metabolic dysregulation in IBS pathology (Han et al 2022a ). The role of R. gnavus (amongst other species) as a potential biomarker for discriminating disease phenotypes was further confirmed in a 16S rRNA gene sequencing-based comparison of gut faecal and mucosa microbiota in newly diagnosed, treatment-naïve adults with IBD or IBS (13 UC, 10 CD, and 26 IBS) and in a healthy group (Cipcic Paljetak et al 2022 ).…”
Section: Association Between R Gnavus and Diseasesmentioning
confidence: 84%
“…The first analyses of the OSCCAR and PRISM cohorts already reported Phascolarctobacterium as one of the two only genera that were significantly reduced in UC and CD patients 37 with no specific mention of Dialister, an observation independently confirmed in other cohorts 38,39 . Subsequent studies also reported concomitant decreased abundances of Phascolarctobacterium and increased Dialister between IBD patients and healthy controls 39,40 . While these studies did point into the direction of a role of intestinal succinate in IBD, our classification into functionally different succinotypes now allows for a mechanistic interpretation of these consistent signals.…”
Section: Discussionmentioning
confidence: 92%
“…The latter four that more abundant in the colitis group were the main causative bacteria of colitis, which led to memory loss, colorectal cancer, appendicitis and dysentery. [ 73,74 ] Conversely, probiotics ( Bifidobacterium , for maintaining the balance of the microbiota) were reduced in the colitis group. After treatment with MeNPs, the level of probiotics increased nearly eightfold (Figure 9D), and the abundance of pathogenic bacteria was also greatly reduced.…”
Section: Resultsmentioning
confidence: 99%